Faktor Determinan yang Mempengaruhi Kepatuhan Ibu Hamil Mengkonsumsi Tablet Zat Besi di Puskesmas Pulau Barrang Lompo Makassar - Rizky Auliah Juniarti; Hadijah (Pusat Riset dan Inovasi Nasional, 2023)
Maternal mortality during childbirth is a global concern, and in Indonesia, this issue remains significant. According to the Ministry of Health (Depkes) in 2020, the primary cause of maternal mortality during childbirth is hemorrhage (28%). Anemia and energy deficiency are the main contributing factors to hemorrhage. Preventing iron-deficiency anemia can be achieved through the use of tablet supplements containing 200 mg ferrous sulfate + 0.25 mg folic acid (Fe tablets). Therefore, the level of coverage and compliance among pregnant mothers in consuming iron tablets becomes an intriguing subject for investigation. This research aims to identify determinant factors influencing the compliance of pregnant mothers in consuming iron tablets at the Barrang Lompo Island Community Health Center in Makassar in the year 2023. Method: This study employs a non-experimental quantitative research design utilizing a cross-sectional approach. The study is conducted at the Maternal and Child Health Clinic of the Barrang Lompo Island Community Health Center in Makassar from April to June 2023. The sample size for this research is 38 individuals, selected using Non-Probability Sampling, specifically Purposive Sampling. The data is analyzed using the chi-square test. Research findings indicate that the factors influencing pregnant mothers' compliance in consuming iron tablets during pregnancy exhibit low p-values. The p-values are as follows: 0.00 for knowledge, 0.01 for attitude, 0.00 for family support, and 0.01 for healthcare provider motivation. This demonstrates a significant relationship between these factors and the compliance of pregnant mothers in maintaining iron tablet intake during pregnancy, at a significance level of α = 0.05. Conclusion: Knowledge, attitude, family support, and healthcare provider motivation significantly influence the compliance of pregnant mothers in consuming iron tablets.